2012
DOI: 10.2165/11635240-000000000-00000
|View full text |Cite
|
Sign up to set email alerts
|

Using the Analytic Hierarchy Process to Elicit Patient Preferences

Abstract: The AHP can easily be used to elicit patient preferences and the study has demonstrated differences between patients and experts. The AHP is useful for policy makers in combining multiple clinical outcomes of healthcare interventions grounded in randomized controlled trials in an overall health economic evaluation. This may be particularly relevant in cases where different outcome measures lead to conflicting results about the best alternative to reimburse. Alternatively, AHP may also support researchers in se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…In the context of this study, we demonstrated that AHP is an appropriate method to estimate group decision and identify patient-relevant characteristics in terms of possible treatment alternatives (5;12;38).…”
Section: Resultsmentioning
confidence: 87%
See 1 more Smart Citation
“…In the context of this study, we demonstrated that AHP is an appropriate method to estimate group decision and identify patient-relevant characteristics in terms of possible treatment alternatives (5;12;38).…”
Section: Resultsmentioning
confidence: 87%
“…Regulatory and reimbursement entities, including the Institute for Quality and Efficiency in Health Care (IQWiG) and the Food and Drug Administration (FDA) have recently required identification and weighting of patient-centered endpoints in health technology assessment (HTA) particularly in the pharmaceutical market (5;6) and medical products (710). To this end, regulatory IQWiG decisions regarding approval, reimbursement or pricing require explicit or implicit trade-offs between the potential benefits and risks, costs and, in certain circumstances, the mode of administration of healthcare delivery.…”
Section: Policy Contextmentioning
confidence: 99%
“…Moreover, in 2017, the last recorded methodological discussion was published and, in this context, the systematic direct integration of patient perspectives was again demanded in several parts of the IQWiG methods paper, e.g., the clear-cut acknowledgement of patient preferences [26]. The first pilot projects concerning the measurement and inclusion of patient preferences in health economic evaluation were published in 2013 (Analytic Hierarchy Process (AHP) [28, 29] and 2014 (Conjoint Analysis) [30, 31]. Although the named projects and discussions seem to lay the basis for the methodologically grounded inclusion of patient perspectives, the first inclusions of patient preferences were recorded in 2017 and 2018 in the field of rare diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Zimmerman et al (2013) found that adult patients currently or previously in treatment for depression generally placed the highest value on the ability to cope with activities of everyday living, and they also preferred being free of depression-related pain and side effects to being free of depressed mood. Another study examined patient preferences for outcomes of taking antidepressant medications and found that patients prioritized —in order of decreasing importance—improvement in depressive symptoms, cognitive function, social function, no anxiety, remission, and no relapse (Hummel et al, 2012). These studies, however, focused on overall group averages rather than individual differences in outcome priorities.…”
Section: Discussionmentioning
confidence: 99%